Beyond traditional lectures: development, analysis, and acceptability of E-learning module in psychiatry - Ajay Thangaraj; Kamatchinathan Premkumar; Vaishali Shanmugam; Sheelapriya G (Asian Journal of Medical Sciences, 2025)
Background: Although digital technologies are increasingly being incorporated into medical education, there is still a lack of substantial evidence comparing the effectiveness of E-learning video modules with traditional lectures in psychiatry education remains limited. This is chiefly significant in the areas such as the Doctor-Patient Relationship and Breaking Bad News. Aims and Objectives: This study aims to develop, implement, and evaluate an E-learning video module designed to enhance psychiatry competency within the Attitude, Ethics, and Communication (AETCOM) framework, with a particular emphasis on the Doctor-Patient Relationship and the process of Breaking Bad News. Materials and Methods: Forty medical students were randomly assigned to one of two learning methods: Traditional lecture-based instruction (Group A, n=20) or an E-learning video module (Group B, n=20). The training focused on Psychiatry competency and the AETCOM module on the Doctor-Patient Relationship, with a special emphasis on Breaking Bad News. Knowledge acquisition was measured using standardized pre-tests and post-tests administrated two weeks after the intervention. In addition, student perceptions were assessed through a semi-structured feedback questionnaire. Results: Both groups demonstrated equivalent baseline knowledge (pre-test scores: 55%). Post-test results revealed significantly higher scores in the E-learning group (93%) compared to the lecture group (77%), representing a mean difference of 16% (P<0.0001, Cohen’s d=1.82). Correlation analysis showed strong positive relationships between perceived engagement and post-test performance (r=0.73, P<0.001). Most students (80%) reported feeling “much more prepared” after completing the E-learning module and valued its self-paced nature (80%). The flexibility for repeated viewing and high engagement levels were identified as key advantages of the E-learning approach. Conclusion: E-learning video modules demonstrate superior effectiveness compared to traditional lectures in psychiatry education particularly in areas such as the Doctor-Patient Relationship and Breaking Bad News, with significantly higher knowledge acquisition and positive student perceptions.